PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KOMPETENSI DASAR MENGIDENTIFIKASI BENTUK PASAR DALAM KEGIATAN EKONOMI MASYARAKAT KELAS VIII-B SMP NEGERI 1 JANGKAR KABUP - Lisma Dian Kartika Sari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This research was conducted to improve student’s learning activity and their learning outcomes in social science subject by using Cooperative Learning Model with Snowball Throwing. This research was Classroom Action Research, by using Kemmis and Mc Taggart model with two cycles. This research was accompanied by research instrument such as observation sheets, interview sheets, and paper based test. The research was conducted in class VIII-B State Junior High School 1 Jangkar, which participated by 26 students. The result of this study showed that student’s learning activity and learning outcomes on social science subject were increased after the implementation of cooperative learning model with Snowball Throwing. The percentage of student’s learning activity in the first cycle was 71,39% with “Quite Active” criteria and learning outcomes mastery obtained 69,23%, whereas the percentage of student’s learning activity on the second cycle increased to 90,87% with “Very Active” criteria and their learning outcomes mastery obtained 92,30%. Thus, it can be concluded that snowball throwing learning model can improve student’s learning activity and learning outcomes